2005
DOI: 10.1108/01437730510575552
|View full text |Cite
|
Sign up to set email alerts
|

A correlation of servant leadership, leader trust, and organizational trust

Abstract: PurposeAims to explore the relationship between employee perceptions of servant leadership and leader trust, as well as organizational trust.Design/methodology.approachUses Laub's Organizational Leadership Assessment along with Nyhan and Marlowe's Organizational Trust Inventory.FindingsPerceptions of servant leadership correlated positively with both leader trust and organizational trust. The study also found that organizations perceived as servant‐led exhibited higher levels of both leader trust and organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
234
1
17

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 385 publications
(290 citation statements)
references
References 65 publications
21
234
1
17
Order By: Relevance
“…Moreover, according to Banutu-Gomez (2004) servant leaders elicits trust in followers because they respond to crisis by owning the problem. Furthermore, because servant leaders lead by setting example, not just talk the talk but walk the walk, empathize with and completely accept their followers, they are able to earn their followers' trust through this kind of servant leader's behavior (Joseph & Winston, 2005).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Moreover, according to Banutu-Gomez (2004) servant leaders elicits trust in followers because they respond to crisis by owning the problem. Furthermore, because servant leaders lead by setting example, not just talk the talk but walk the walk, empathize with and completely accept their followers, they are able to earn their followers' trust through this kind of servant leader's behavior (Joseph & Winston, 2005).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The influence of different leadership behaviour to organisational citizenship behaviour is significant. The study found that there are very significant correlation between leadership with subordinates exchange activities and organisational citizenship behaviour, and this relationship can adjust by subordinates exchange conscious (Joseph & Winston, 2005). In addition, the high-performance expectation and the support of the leadership behaviour also have correlation between organisational citizenship behaviour, and all these need further research.…”
Section: Antecedent Variables Of Organisational Citizenship Behaviourmentioning
confidence: 99%
“…Ayrıca, Joseph ve Winston (2005) taraflarından yapılan araş-tırmada yöneticiye ilişkin hizmetkâr liderlik algılarının lidere ve örgüte gü-venle pozitif yönde anlamlı ilişki içerisinde olduğu sonucuna varılmıştır.…”
Section: İlkokul Yöneticilerinin Sâhip Olması Gereken Hizmetkâr Liderunclassified